An Overview of Automobile Noise and Vibration Control. (June 2013) - Mohanty, A. R.; Fatima, S.
In this paper the current state-of-the-art techniques in automobile noise and vibration control are presented. Automobile designers and manufacturers have to pay attention to the global competition of their products, adherence to legislative regulations and passenger/driver comfort while designing an automobile and its components. Designers can take advantage of efficient numerical modeling techniques so that in before the prototype of the automobile is produced, the design can be tweaked and modified by using computer aided models to optimize the design with a target of achieving low noise and vibration levels in the prototype. Here, examples of some typical cases are provided where optimum levels of noise and vibration level are obtained in the design of automobile components using computer aided engineering techniques